PARP‐1 regulates DNA repair factor availability. Issue 12 (22nd November 2018) - Schiewer, Matthew J; Mandigo, Amy C; Gordon, Nicolas; Huang, Fangjin; Gaur, Sanchaika; de Leeuw, Renée; Zhao, Shuang G; Evans, Joseph; Han, Sumin; Parsons, Theodore; Birbe, Ruth; McCue, Peter; et al.
Abstract: PARP‐1 holds major functions on chromatin, DNA damage repair and transcriptional regulation, both of which are relevant in the context of cancer. Here, unbiased transcriptional profiling revealed the downstream transcriptional profile of PARP‐1 enzymatic activity. Further investigation of the PARP‐1‐regulated transcriptome and secondary strategies for assessing PARP‐1 activity in patient tissues revealed that PARP‐1 activity was unexpectedly enriched as a function of disease progression and was associated with poor outcome independent of DNA double‐strand breaks, suggesting that enhanced PARP‐1 activity may promote aggressive phenotypes. Mechanistic investigation revealed that active PARP‐1 served to enhance E2F1 transcription factor activity, and specifically promoted E2F1‐mediated induction of DNA repair factors involved in homologous recombination (HR). Conversely, PARP‐1 inhibition reduced HR factor availability and thus acted to induce or enhance "BRCA‐ness". These observations bring new understanding of PARP‐1 function in cancer and have significant ramifications on predicting PARP‐1 inhibitor function in the clinical setting. Synopsis: By integrating data generated in model systems and human tissues, and in silico analyses of cancer patient‐derived data, this study reveals that PARP‐1 affects the expression of DNA repair factors through E2F1. Co‐targeting PARP‐1 and the cell cycle machinery could be a novel treatment strategy. PARP‐1 enzymatic and transcriptional regulatory functions are elevated as a function of prostate cancer (PCa) progression. PARP‐1 impacts the transcriptional activity of E2F1, including regulation of cell cycle and DDR gene expression. HR factors are frequently transcriptionally deregulated in PCa, which is enriched in PCa progression. Transcriptional regulation of DNA repair factor expression by PARP‐1 impacts the response to PARPi. Abstract : By integrating data generated in model systems and human tissues, and in silico analyses of cancer patient‐derived data, this study reveals that PARP‐1 affects the expression of DNA repair factors through E2F1. Co‐targeting PARP‐1 and the cell cycle machinery could be a novel treatment strategy.